Studying the Difference between the Ability of Honeyand Hibiscus Flower Nanoparticles to Protect AgainstRadiation Risks - Ashour, Omar S.; Al-Mashhadani, Asia H. (Iraqi Journal of Science, 2025)
Honey and hibiscus flower nanoparticles have numerous unique characteristics, such as biocompatibility; they are excellent agents for biological applications. The aim of this study is to investigate honey and hibiscus flower nanoparticles for 2, 2- diphenyl-1-picryl-hydrazyl-hydrate (DPPH) free radical scavenging activity and their ability to offer protection against ionizing radiation (gamma ray). In this research, natural nanoparticles prepared from honey and plants (hibiscus flower) were used for the purpose of studying their effectiveness as antioxidants in water by scavenging free radicals resulting from radiation. In vitro antioxidant activity study of honey and hibiscus flower nanoparticles has shown good free radical scavenging activity for DPPH radical assayed within a concentration range of (0.5 - 2.5) x10-4 g/l, for honey nanoparticles and range (0.1-0.5)x10-4g/l for hibiscus flower nanoparticles. The absorbance and inhibition indicating this finite range of concentration is suitable for scavenging free radicals, also nanoparticles were found to have significant natural antioxidant capacity and thus can be used as potential radical scavenger against deleterious damages caused by the free radicals. Hibiscus flower nanoparticles have shown higher ability for free radical inhibition of 93.40% at 0.5x10-4 g/l, than honey nanoparticles of 49.80% at 2.5×10-4g/l.